Multiple genetic modifications of the erythromycin polyketide synthase to produce a library of novel “unnatural” natural products - McDaniel, Robert (The National Academy of Sciences, 1999)
The structures of complex polyketide natural products, such as erythromycin, are programmed by multifunctional polyketide synthases (PKSs) that contain modular arrangements of functional domains. The colinearity between the activities of modular PKS domains and structure of the polyketide product portends the generation of novel organic compounds—“unnatural” natural products—by genetic manipulation. We have engineered the erythromycin polyketide synthase genes to effect combinatorial alterations of catalytic activities in the biosynthetic pathway, generating a library of >50 macrolides that would be impractical to produce by chemical methods. The library includes examples of analogs with one, two, and three altered carbon centers of the polyketide products. The manipulation of multiple biosynthetic steps in a PKS is an important milestone toward the goal of producing large libraries of unnatural natural products for biological and pharmaceutical applications.